Flow Injection Chemiluminescence Determination of Paraquat using Luminol and Ag(III) Complex - Liu, Fei; Shi, Hongmei; Xu, Xiangdong; Kang, Weijun; Li, Zhanhua (Asian Journal of Chemistry, 2010)
A novel flow injection chemiluminescence system is described for the determination of paraquat. The method is based on the fact that paraquat can enhanced the chemiluminescence intensities of Ag(III)-luminol in alkaline solution. The optimum conditions for the chemilu-minescence emission are evaluated. Paraquat can be determined over the concentration range of 5.0 × 10-6- 1.0 × 10-3 M with a correlation coefficient of 0.999 and a detection limit of 2.0 × 10-7 M (S/N = 3). The relative standard deviation for 11 repetitive determination of 2.0 × 10-4 M paraquat is 1.01 %. The proposed method offers the potential advantages of high sensitivity, simplicity and rapidity for paraquat determination and the utility of this method is demonstrated by detecting paraquat in pesticide and vegetable samples.